Características de utilización de los esquemas terapéuticos de primera elección para el cáncer de cérvix en la unidad de mezclas oncológicas del Instituto Regional de Enfermedades Neoplásicas - IREN - Norte Dr. Luis Pinillos Ganoza, periodo 2011-2015” - Santa Cruz Espinoza, José Norberto (2016)
This study purpose to identify therapeutic scheme for the treatment of cervical cancer in the Regional Institute of Neoplastic Diseases "Dr. Luis Pinillos Ganoza "over the years of 2011-2015. This information was obtained from the database of the Technical Office Registration of this Institute, discarding those patients whose records were illegible and / or not completed the treatment, schemes first identified choice were: CDDP (Cisplatin), CDDP + 5-FU (Cisplatin + 5-fluorouracil), PCTX (paclitaxel) and CBDCA + PCTX (carboplatin plus paclitaxel) .In 2011 were identified 188 schemes, year 2012 167 schemes were used in the year 2013 224 schemes were used in the year 2014 325 schemes were used and in 2015 254 schemes were used. In total for treatment of cervical cancer 1068 schemes were used. Using the Pareto rule was determined that the scheme most often use in 2011 was CDDP (cisplatin) (37.23%) followed by CDDP + 5-FU (30.32%), PCTX (10.11%), CBDCA +PCTX ( 22.34%). for 2012 the scheme with greater frequency of use was CDDP (cisplatin) (35.93%) followed by CDDP + 5-FU (26.94%), PCTX (7.19%), CBDCA + PCTX (29.94%). in 2013 the scheme with greater frequency of use was CDDP (cisplatin) (35.71%) followed by CDDP + 5-FU (28.57%), PCTX (11.16%), CBDCA + PCTX (24.55%). 2014 the scheme with more frequent use was CDDP (cisplatin) (31.91%) followed by CDDP + 5-FU (29.79%), PCTX (13.62%), CBDCA + PCTX (24.68%). Finally 2015 the scheme with most frequently used was CDDP (cisplatin) (32.28%) followed by CDDP + 5-FU (28.35%), PCTX (13.78%), CBDCA + PCTX (25.59%). with respect to the evolution of using schemes therapeutic was observed that CDDP (cisplatin) predominated scheme as the scheme most used in the present study period but irregular trend. Schemes CDDP + 5-FU (5-fluorouracil + Cisplatin) are prone irregular schemes but they are very effective according to the stadium and safety of the drugs used in the scheme. The PCTX (Paclitaxel) scheme presented an increase in the frequency of use because this scheme is used in metastatic cancer as a palliative and there were no early detection of the disease. The variation in the frequency of use of therapeutic schemes is subject to stage of disease, availability of antineoplastic drugs and clinical criteria of specialist medical personnel